Marijuana use and protective behavioral strategies in Argentinean college students - Rinaldi, Carolina (2019)
The Protective Behavioral Strategies Scale for Marihuana [PBSM] measures the frequency of engaging in specific behaviors to reduce or minimize the negative consequences of marijuana. Previous studies, conducted mostly with college students from U.S., showed a robust association between PBSM scores and marijuana outcomes. This study examined the use of protective behavioral strategies and its association with marijuana use (i.e., frequency and quantity) and marijuana-related negative consequences in 158 freshman college students (51.3% women, M age = 20.08 ± 4.18) from Argentina. College freshman that reported using marijuana at least once with the previous month completed an online survey that assessed frequency (i.e., number of days) and quantity of marijuana use (i.e., grams of marijuana within each day of a typical week), marijuanarelated negative consequences, and the PBSM. Close to 30% of the sample reported >5 days of marijuana use during the previous month and close to 20% reported using more than 3 grams during a typical week of marijuana use. Overall, marijuana use and PBS use were statistically similar between men and women. PBS was, in both men and women, negatively and significantly associated with frequency of use and – in men only – with quantity of marijuana use, but not with the number of marijuana-related negative consequences. Conclusions: Frequency of marijuana-related PBS was, unlike previous studies that assessed this variable in the context of alcohol use, similar between men and women. Moreover, and despite a general protective effect of PBS on marijuana use, the association between PBS and marijuana use seems to be stronger for men than for women. The promotion of PBS seems a promising intervention to reduce marijuana use.